The Principle of Bal Tashchit in Deuteronomy: A Sacred Call for Wartime Eco-Sensitivity - Biju Karukappallil (Journal of Dharma, 2025)
This article provides a closer look at the prohibition of cutting down fruit trees in Deuteronomy 20:19-20 in the context of two challenging crises that threaten the stability and wellbeing of the whole humanity: armed conflicts and environmental destruction. Briefly analyzing the historical context of the wartime scorched-earth tactics, and having considered similar texts in the Pentateuch, the injunction in Deuteronomy is pointed out as one of the earliest legislative attempts to execute environmental restraint during armed conflicts. This prohibitive precept is the basis of the rabbinic principle of ‘Bal Tshchit’ - ‘do not destroy’- by which the ban on violence was broadened to all spheres of life. Situating this within the contemporary context of international conflicts shows the necessity to re-consider the Biblical foundations of ecological sensitivity that helps define environmental protection as a sacred duty. In this light, the ancient commandment offers a sacred call for integrating environmental reverence into modern visions of peace and justice.